Ultrasound Used for Diagnostic Imaging Facilitates Dendritic Branching of Developing Neurons in the Mouse Cortex - Papp, Tamas; Ferenczi, Zsuzsanna; Szilagyi, Bernadette; Petro, Matyas; Varga, Angelika; Kókai, Eva; Berenyi, Ervin; Olah, Gabor; Halmos, Gabor; Szucs, Peter; Meszar, Zoltan (Frontiers in Neuroscience, 2022)
Neuronal differentiation and synaptogenesis are regulated by precise orchestration of intrinsic and extrinsic chemical and mechanical factors throughout all developmental steps critical for the assembly of neurons into functional circuits. While ultrasound is known to alter neuronal migration and activity acutely, its chronic effect on neuronal behavior or morphology is not well characterized. Furthermore, higher frequency (3-5 MHz) ultrasound (HFU) is extensively used in gynecological practice for imaging and while it has not been shown harmful for the developing brain, it might be associated with mild alterations that may have functional consequences. To shed light on the neurobiological effects of HFU on the developing brain we examined cortical pyramidal cell morphology in a transgenic mouse model, following a single and short dose of high-frequency ultrasound. Layer V neurons in the retrosplenial cortex of mice embryos were labeled with green and red fluorescent proteins by in utero electroporation at the time of their appearance (E14.5). At the time of their presumptive arrival to layer V (E18.5) HFU stimulation was performed with parameters matched to those used in human prenatal examinations. On the third postnatal day (P3) basic morphometric analyses were performed on labeled neurons reconstructed with Neurolucida. Low-intensity HFU treated cells showed significantly increased dendritic branching compared to control (non-stimulated) neurons and showed elevated c-fos immunoreactivity. Labeled neurons were immunopositive for the mechanosensitive receptor TRPC4 at E18.5, suggesting the role of this receptor and the associated signaling pathways in the effects of HFU stimulation.